Artificial Intelligence-Assisted Conductive Hydrogel Dressings for Refractory Wounds Monitoring - Yumo She; He Liu; Hailiang Yuan; Yiqi Li; Xunjie Liu; Ruonan Liu; Mengyao Wang; Tingting Wang; Lina Wang; Meihan Liu; Wenyu Wan; Ye Tian; et al. (Nano-Micro Letters)
Highlights The advantages and selection of conductive materials, including conductive polymers and inorganic nanoparticles are discussed in detail. Signal output categories of the conductive hydrogel dressing to monitor wound conditions, notably, AI-based wound monitoring and prediction is highlighted. The review analyzes the application, current challenges and potential prospects of conductive hydrogel dressings for the different refractory wounds monitoring.